An intensive monitoring of adverse drug reaction in indoor patients of medicine department at tertiary care teaching hospital - Darji, Nishita H.; Jadav, Shilpa; Doshi, Chintan; Hedamba, Rutvij; Mistry, Rusva; Trivedi, Hiren (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Use of drugs itself may result into illness and death due to their adverse effects. In India 10-20% of inpatients developed adverse drug reactions. Most of these problems can be overcome by undertaking hospital based intensive monitoring. Objective of this study was to estimate the incidence and document the spectrum of ADRs in studied patients in terms of causality, severity, frequency, type and preventability. A prospective, observational, single centre study conducted among the indoor patients of the department of general medicine, Guru Gobind singh government hospital, Jamnagar over a period of 12 months. Methods: Admitted patients who either had developed a clinically suspected ADR after admission (group A) or were admitted primarily because of an ADR (group B) were included. In all ADR related patients the necessary data was recorded on a pre-designed case record form, NCC-PvPI form and analysis was done. Results: Total 3566 patients were screened. 87 patients had 101 ADRs, among them 62 from group A and 25 from group B with 2.44% incidence. In causality, by WHO-UMC and by naranjo scale most common ‘probable’ category in group A (54.7%) and group B (50%) and 89.9% group A and 84.6% in group B respectively.95.05% ADRs were ‘Not preventable’. Hartwig seigle’s scale maximum ADRs 65.4% ADRs in group A and 73.1% in group B were ‘moderate’ in severity. Conclusions: Intercurrent illness, longer hospital stay and poly pharmacy was playing a major role in occurrence of multiple ADRs with 2.44% incidence in our setup.